Here today [videorecording (DVD)] - Crystal, Billy; Crystal, Billy; Haddish, Tiffany, 1979-; Badgley, Penn, 1986-; Benanti, Laura; Zweibel, Alan (Sony Pictures Home Entertainment, 2021)
When veteran comedy writer Charlie Burnz meets New York singer Emma Payge, they form an unlikely yet hilarious and touching friendship that kicks the generation gap aside and redefines the meaning of love and trust.